Isolation and Characterisation of Culturable Thermophilic Cyanobacteria from Perak Hot Springs and their Plant Growth Promoting Properties Effects on Rice Seedlings (Oryza sativa L.) - Clement Kiing Fook Wong; Tzu Yee Chong; Ji Tan; Wey Lim Wong (Tropical Life Sciences Research, 2023)
Malaysia is home to a number of hot springs that are rich in microbial diversity including the photosynthetic cyanobacteria. Although this microbial community has been characterised based on metagenomics approach, the culturable thermophilic isolates have not been isolated and characterised extensively. Compared to the mesophiles, information on plant growth promoting (PGP) properties of these thermophiles remain largely untapped. As the amount of arable land for microbial bioprospecting is decreasing due to extensive human activities, the search for alternative source for microbial strains with PGP properties is important for the development of potential biofertilizers. This study sought to isolate and characterise culturable cyanobacteria strains from two local hot springs – Sungai Klah (SK) and Lubuk Timah (LT) located in Perak using morphological and molecular methods. The IAA production from the axenic cultures were measured. The PGP properties were also measured by priming the rice seeds with cyanobacterial water extracts. A total of six strains were isolated from both hot springs. Strains LTM and LTW from LT were identified as Leptolyngbya sp. whereas strains SEM, SEH, STH and STM were identified as Thermosynechococcus elongatus. All six strains produced IAA ranged from 670.10 pg/ ?L to 2010 pg/?L. The water extracts were found to increase the seed amylase activity of the rice seeds from 5th day of germination (DAG) to 10th DAG. In general, the IAA production and increased seed amylase activity might have contributed in enhancing the longest root length, shoot length and root-to-shoot (RS) ratio. To conclude, the thermophilic cyanobacteria from hot springs can be further exploited as a novel source of PGP microbes for the development of biofertilisers.